Anatomical variation of maxillary first molar with two roots and two canals: a rare case report - Sadhana SM; Mujeeb, Abdul; Ishaque, Aquib (IIUM Journal of Orofacial and Health Sciences, 2026)
This case report describes the endodontic management of a maxillary first molar with an unusual anatomical configuration, consisting of a single buccal root and a single palatal root, each containing one root canal with a Vertucci Type I configuration. Cone-beam computed tomography (CBCT) confirmed the atypical root morphology and facilitated appropriate treatment planning. The case highlights the significance of recognizing anatomical variations and the utility of advanced imaging techniques in complex endodontic cases.